Penggunaan Media Komunikasi Bagi Remaja Perempuan Dalam Pencarian Informasi Kesehatan - Ditha Prasanti (LONTAR: Jurnal Ilmu Komunikasi, 2018)
Health information becomes important, not only for the sick, the elderly, or the children, but also for young women. Especially considering the new media era that developed more sophisticated along with the development of technology in his day. Likewise, it happens with the writer's research informant who has a new method in the search for health information.The research review that has been done in this article is the use of female teen communication media in the search for health information. The purpose of this research is to know the communication media used by female teenager in searching health information.  The results of the research have shown that the female teenagers who become informants of this research writer use various communication media. Among young women who are studying in health majors choose to use online journal literature only.